Recent Insights and Clinical Status on Novel Mefenamic Acid Nanocarriers for the Treatment of Rheumatoid Arthritis - Tyagi, Sunayana; Pande, Milind Sharad; Islam, Mojahidul (Current Nanomaterials, 2024)
Joint structure and performance can be compromised by the systemic inflammatory disorder rheumatoid arthritis, which destroys articular cartilage and erodes periarticular bone. However, due to their systemic processes, short half-lives, and poor bioavailability, the anti-inflammatory medicines and biological agents now utilized for the treatment of rheumatoid arthritis (RA) are unable to preferentially target inflamed joints. Anti-inflammatory medicines have made use of nanoparticle-mediated drug delivery methods. The role that inflammation plays in the genesis of disease has had far-reaching repercussions, including its ability to influence the development of disorders as diverse as inflammatory bowel disorder, RA, and osteoarthritis. In the treatment of RA, nanomaterials have the potential to both increase the absorption of the medication and selectively target the damaged joint tissue. Designer nanoparticles now have the ability to engage more thoroughly with their biological targets and a wider variety of diseases. These nanoparticles have a comparable size range and surface properties that can be modified. In this review, we have discussed the progress that has been made and the hurdles that remain in the use of nanomaterials in the treatment of RA, specifically in relation to mefenamic acid.
Keywords: nanoparticle